Sosialisasi Makanan Sehat Dan Dampak Stunting Terhadap Pertumbuhan Perkembangan Anak Usia Dini - Saputra, Dwi Yudha (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Stunting is a serious problem in the growth and development of early childhood which can have an impact on their health and quality of life. Therefore, it is necessary to carry out effective outreach and intervention to prevent stunting. The KKN (Real Work Lecture) program in Karangrowo Undaan Village is a forum for implementing this effort. In this context, PMT (Extension and Socialization of the Supplemental Food Program) is the main instrument in educating mothers of toddlers about stunting and the importance of balanced nutrition. This abstract describes the stages of the KKN program which involves counseling, discussion, measuring children's height and weight, as well as the practice of preparing a healthy, nutritious lunch menu. Through the